Visual analysis of particle behaviors to understand combustion simulations - Wei, Jishang (IEEE computer graphics and applications, 2012)
A dual-space method enables effective visual analysis of particles' spatial movement and attribute evolution. Intuitive interaction tools integrate users' domain knowledge to steer classification. This method has been used to analyze combustion simulations and is applicable to other scientific simulations involving particle-data analysis